Innovative and socially motivated village development in a regional context: The Grythyttan case - Per Frankelius; Fredrik Eliasson (European Regional Science Association (ERSA), 2010)
The typical study object in business administration is a private company. It is also common in that discipline to analyse groups of companies like networks or clusters. Moreover there are many studies on public and idealistic organizations. In this study however, we will not focus on companies or organizations. Rather we want to shed light over villages (or small towns). The study object is "village development", and especially such kind that is a) socially motivated, b) intended and conscious, and c) has parallels to innovation and entrepreneurship. Most studies on local communities are based on political science, geography, economics, or architecture. Classical references include Marshall (1919) and Beccattini (2004) on industrial districts or von Thünen (1826) on economic geography. Most studies (except architecture) are characterized by a high level of abstraction. One main point in this paper is the analysis of village development from a strategic perspective, and therefore the study is based primary on business administration theory. Villages are not the core interest of the discipline business administration. There exists however exceptions like Johannisson (1978) on local networks or Kotler et al (1993) on "place marketing". In this paper we focus on Grythyttan. We relate that village to another village in the same region. The two villages experienced decline from the years dominated by industrial businesses. But while Grythyttan has transformed to a gastronomic centre there are few positive signs of development in the other village. The question is: Why? The first aim is to derive success factors, but also other factors (and pattern of events) that affected the process. The second aim is to develop a visual language for description of village development processes. A third aim is to connect the micro level analysis with some meso and macro aspects of the region to which Grythyttan belongs. The empirical material was collected through semi-structured interviews with key persons related to the case during the years 2002-2010. The data collection also included participation, photographing and archive-work. Books, reports and statistical databases were used as well.
Keywords: 330